กลยุทธ์การบริหารโรงเรียนมัธยมศึกษาสู่ความเป็นเลิศตามแนวคิดทักษะนวัตกรสังคม - ภาณุภัทร ลิ้มจำรูญ (จุฬาลงกรณ์มหาวิทยาลัย, 2020)
The objectives of this research were 1) to study the conceptual framework of school management towards excellence and social innovator skills. 2) to analyze the strengths, weaknesses, opportunities and threats of school administration towards excellence according to the concept of innovative skills. 3) to develop strategies for managing secondary schools towards excellence based on the concept of social innovator skills. The methodology used in this research was the multiphase mixed methods design consisting of qualitative research, quantitative research and mixed methods research. The samples were 92 secondary schools providing for Mattayomsuksa 1 - 6 students under the Office of the Basic Education Commission, the Ministry of Education. The research instruments were a form of conceptual framework assessment, a questionnaire, a form of suitable and feasible of strategy assessment, and an expert group discussion. The statistics that used to analyze the data were frequency, percentage, mean, standard deviation (SD), essential needs index (PNImodified), and content analysis. The results of this research revealed that: 1) the framework of school management for excellence consists of 7 factors; leadership, strategy, students and stakeholders, measurement, analysis, and knowledge management, workforce, operations, and results. Moreover, the framework for social innovators skills consisted of 5 factors; creative visionary, deep collaboration, systematic thinking, empathetic activism, and entrepreneurship through a suitable assessment from professional experts. 2) The three factors found on strengths, weaknesses, opportunities, and threats of school management towards excellence according to the social innovator skills concept were (1) school management towards excellence has four weaknesses which are operations, results, strategies, and workforce. But, the three strength points are measurement, analysis, and knowledge management, students and stakeholders, and leadership in order. (2) Social innovator skills contain both one weak and four strength points. Entrepreneurship is that weak point. The strengths can be divided into four factors; systematic thinking, creative visionary, empathetic activism, and deep collaboration respectively. (3) The external environment has some threats which are politics and state policy and economical conditions. As for social and technological conditions are accounted for an opportunity. 3) The secondary school management strategies for excellence based on the concept of social innovator skills have 5 main strategies, 10 sub strategies and 43 approaches. The first main strategy is to enhance operational efficiency towards excellence in student development according to the concept of 3 aspects of social innovator. The second main strategy is to raise the results of student development according to the concept of 3 aspects of social innovator skills. The third main strategy is to initiate management strategies for excellence in student development according to the concept of 3 aspects of social innovator skills. The fourth main strategy is to transform the management process to excellence in personnel according to the concept 3 aspects of social innovator skills. The fifith main strategy is to operate the measurement of analysis and knowledge management according to the concept of 3 aspects of social innovator skills.